Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am trying to calculate $\kappa^\lambda = \aleph_{\omega_1}^{\aleph_0}$.

I know that if $\kappa$ is a limit cardinal and $0 < \lambda < \mathrm{cf}(\kappa)$ then $\kappa^{\lambda} = \displaystyle \sum_{\alpha < \kappa} |\alpha|^{\lambda}$.

Hence $ \aleph_{\omega_1}^{\aleph_0} = \displaystyle \sum_{\alpha < \aleph_{\omega_1}} |\alpha|^{\aleph_0}$.

I also know that if $\kappa, \lambda$ are infinite cardinals then $(\kappa^+)^\lambda = \kappa^\lambda \cdot \kappa^+$ so that $\aleph_\alpha^{\aleph_0} = \aleph_\alpha \cdot \aleph_{\alpha-1}^{\aleph_0} = \aleph_\alpha \cdot \aleph_{\alpha-1} \cdot \aleph_{\alpha-2}^{\aleph_0} = \dots = \aleph_\alpha \cdot \aleph_{\alpha-1} \cdot \dots \cdot \aleph_{0}^{\aleph_0} = \aleph_\alpha$.

Hence $ \aleph_{\omega_1}^{\aleph_0} = \displaystyle \sum_{\alpha < \aleph_{\omega_1}} |\alpha|^{\aleph_0} = \sum_{\alpha < \aleph_{\omega_1}} |\alpha| = \sum_{\alpha < \omega_1} \aleph_{\alpha}$.

Since for infinite cardinals $\lambda \le \kappa$ we have that $\lambda + \kappa = \kappa$, $\displaystyle \sum_{\alpha < \omega_1} \aleph_{\alpha} = \sup_{\alpha < \omega_1} \aleph_{\alpha} = \aleph_{\omega_1}$.

Hence $\aleph_{\omega_1}^{\aleph_0} = \aleph_{\omega_1}$. Is this correct? This is an exercise in Just/Weese and the hint is "Assume GCH". I don't think I have used GCH so I suspect I am missing something. Thanks for your help.


Edit

I have used a different method to compute it and have reached the same result (although I still don't know whether this is correct):

By Tarski's theorem, $\aleph_{\omega_1}^{\aleph_0} = \displaystyle \sum_{\alpha < \aleph_{\omega_1}} |\alpha|^{\aleph_0}$.

Since $|\alpha|^{\aleph_0} \le \aleph_{\omega_1}$ for all $\alpha < \aleph_{\omega_1}$ we get $\displaystyle \sum_{\alpha < \aleph_{\omega_1}} |\alpha|^{\aleph_0} \leq \aleph_{\omega_1}$. Of course, $\aleph_{\omega_1} \leq \aleph_{\omega_1}^{\aleph_0}$.

Hence $\aleph_{\omega_1} = \aleph_{\omega_1}^{\aleph_0}$.

share|improve this question
2  
$\aleph_\alpha^{\aleph_0} = \aleph_\alpha \cdot \aleph_{\alpha-1}^{\aleph_0} = \aleph_\alpha \cdot \aleph_{\alpha-1} \cdot \aleph_{\alpha-2}^{\aleph_0} = \dots = \aleph_\alpha \cdot \aleph_{\alpha-1} \cdot \ldots \cdot \aleph_{0}^{\aleph_0} = \aleph_\alpha$ is possible only for $\alpha=\omega+n$ for some $n\in\omega$. (And I really don’t understand the downvote that I just cancelled.) –  Brian M. Scott Dec 17 '12 at 10:08
1  
I would change the notation to $\alpha+1$ and $\alpha$ rather than $\alpha$ and $\alpha-1$. You can't really write $\omega+\omega-1$. –  Asaf Karagila Dec 17 '12 at 10:13
    
@BrianM.Scott Thank you! But I could do $$ \aleph_{\omega_1}^{\aleph_0} = \displaystyle \sum_{\alpha < \aleph_{\omega_1}} |\alpha|^{\aleph_0} = \sum_{\alpha < \aleph_0} |\alpha|^{\aleph_0} + \sum_{\alpha < \aleph_{\omega_1}} |\alpha|^{\aleph_0} = \aleph_1 + \sum_{\alpha < \aleph_{\omega_1}} |\alpha|^{\aleph_0} $$ and still arrive at the same result. (In fact, I considered this splitting up of the sum to reach what I posted above.) –  Matt N. Dec 17 '12 at 10:14
    
@AsafKaragila You are right. –  Matt N. Dec 17 '12 at 10:15
    
I don’t see how this decomposition helps you: it just tells you that $\omega_1\le(\omega_{\omega_1})^\omega$, which you knew already. –  Brian M. Scott Dec 17 '12 at 10:17
show 1 more comment

2 Answers

up vote 2 down vote accepted

The reason you have to use GCH is that it is consistent that $2^{\aleph_0}=\aleph_{\omega_2}$. In this case the proof fails, simply because $\aleph_0^{\aleph_0}$ is very big compared to $\aleph_{\omega_1}$.

I suppose that the authors chose to use GCH in order to ensure that no cardinal misbehaves in this aspect. It might be the case, after all, that $\aleph_\omega^{\aleph_0}$ is very big (if things go bad enough).

Furthermore what you have written about the exponentiation is true in the case where $\kappa$ is a strong limit. It might not be the case for $\aleph_{\omega_1}$, but it is always the case under GCH.


Okay so we assumed GCH, now we have that $\kappa^{\aleph_0}\leq\kappa^+$, and equality holds if and only if $\operatorname{cf}(\kappa)=\aleph_0$.

Given $\aleph_{\alpha}^{\aleph_0}$ if $\alpha$ is a limit then this simply equal to $\aleph_{\alpha+1}$; but if not then there is some $\delta$ which is a limit and $n\in\omega$ such that $\alpha=\delta+n$. Now show by induction, as you did in your post (the part where you subtract from the index) that $\aleph_\alpha^{\aleph_0}=\aleph_\alpha\cdot\ldots\cdot\aleph_\delta^{\aleph_0}=\aleph_\alpha$.

share|improve this answer
    
So the result is correct? (I found a different way to reach the same result and added it to my question.) –  Matt N. Dec 17 '12 at 11:41
    
@Matt: Yes. Assuming $\aleph_{\omega_1}$ is a strong limit, which follows from GCH, the result is correct. Note that you only used that in your approach, which is fine. –  Asaf Karagila Dec 17 '12 at 11:42
add comment

You want $(\omega_{\omega_1})^\omega$, and you’ve established that $$(\omega_{\omega_1})^\omega=\sum_{\alpha<\omega_{\omega_1}}|\alpha|^\omega\;.\tag{1}$$ Now what if $2^\omega=\omega_{\omega_1+1}$? This is consistent with ZFC, and if it holds, then clearly the righthand side of $(1)$ is at least $\omega_{\omega_1+1}>\omega_{\omega_1}$.

Added: You can extend $(1)$:

$$(\omega_{\omega_1})^\omega=\sum_{\alpha<\omega_{\omega_1}}|\alpha|^\omega\le\sum_{\xi<\omega_1}\omega_\xi^+\cdot(\omega_\xi)^\omega\le\omega_{\omega_1}\cdot\sum_{\xi<\omega_1}(\omega_\xi)^\omega\le\omega_{\omega_1}\cdot\sup_{\xi<\omega_1}(\omega_\xi)^\omega\le(\omega_{\omega_1})^\omega\;,$$

so $$(\omega_{\omega_1})^\omega=\omega_{\omega_1}\cdot\sup_{\xi<\omega_1}(\omega_\xi)^\omega\;.$$

Under GCH you have $(\omega_{\xi+1})^\omega=\omega_{\xi+1}$ and $(\omega_\xi)^\omega=\omega_\xi^+=\omega_{\xi+1}$ when $\xi<\omega_1$ is a limit ordinal, so

$$(\omega_{\omega_1})^\omega=\omega_{\omega_1}\cdot\sup_{\xi<\omega_1}\omega_{\xi+1}=\omega_{\omega_1}\;.$$

share|improve this answer
    
@Matt: Apparently you were going back and forth with Asaf while I was typing this, but here it is for what it’s worth. –  Brian M. Scott Dec 17 '12 at 11:57
    
I didn't get pinged! Thanks for replying and editing your answer! –  Matt N. Dec 17 '12 at 19:25
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.